2016
DOI: 10.1177/1066480716662652
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Interpretive Phenomenological Analysis in Couple and Family Therapy Research

Abstract: This article proposes a research methodology that is newer to the field of couple and family therapy (CFT) research called interpretive phenomenological analysis (IPA). Researchers exploring CFT research continue to establish the efficacy of couple and family interventions in a context that favors a positivist view of phenomena. This research continues to be critical for establishing the role of CFT in the field of mental health as well as further clarifying which interventions are best for specific clinical i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 36 publications
1
25
0
1
Order By: Relevance
“…To align fully with IPA’s idiographic nature, each case is examined independently and thoroughly for themes before moving on to explore patterns between cases. As already indicated, IPA studies also prioritize an examination of convergence and divergence, illuminating ways in which participants’ perceptions of the experience are similar and different (Allan & Eatough, 2016; Pietkiewicz & Smith, 2014). For example, Chan (2018) found that all participants referenced and reflected on their experiences of maleness (i.e., convergence), but that the degree to which maleness was experienced as a privilege differed (i.e., divergence).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To align fully with IPA’s idiographic nature, each case is examined independently and thoroughly for themes before moving on to explore patterns between cases. As already indicated, IPA studies also prioritize an examination of convergence and divergence, illuminating ways in which participants’ perceptions of the experience are similar and different (Allan & Eatough, 2016; Pietkiewicz & Smith, 2014). For example, Chan (2018) found that all participants referenced and reflected on their experiences of maleness (i.e., convergence), but that the degree to which maleness was experienced as a privilege differed (i.e., divergence).…”
Section: Discussionmentioning
confidence: 99%
“…Idiography can be defined as the study of the particular versus the general (Smith et al, 2009). Whereas traditional phenomenological approaches emphasize the essence of a phenomenon as perceived or experienced by a particular group of people, IPA examines the convergence and divergence of perceptions or experiences across a sample of individuals (Allan & Eatough, 2016; Pietkiewicz & Smith, 2014; Smith, 2011; Smith et al, 2009). According to Pietkiewicz and Smith (2014), the intentionality of idiography is to equally highlight and value each case and, subsequently, each participant.…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…Interpretative phenomenological analysis (IPA) (Smith & Shinebourne, 2012) is a method of thematic analysis which aims to describe the meaning of experience through in-depth, reflective processes (Smith, 2018). IPA is increasingly being applied in healthcare research (Peat, Rodriguez, & Smith, 2019) and family therapy research (Allan & Eatough, 2016) to understand experiences which may be emotionally complex. This method of thematic analysis appears to be useful for exploring in-depth individual processes and responses, and includes idiographic responses during interviews (Allen, Burbach, & Reibstein, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The key elements of IPA are that: it is an inductive approach; participants are experts on their own experience and are recruited because of their expertise in the phenomenon being explored; researchers analyze data to identify what is distinct (idiographic study of persons) while balancing that with what is shared across the sample; and the analysis is interpretive, grounded in examples from the data, and plausible to the participants, supervisors, and general public (Smith, Flowers, and Larkin, 2009). Shaw (2001) explains that the focus on individuals' experiences in IPA and the exploration of meaning making processes that are situated in participants' many cultural roles provides rich and diverse data that can be explored in depth making it appropriate for CFT research (Allan & Eatough, 2016).…”
Section: Methodsmentioning
confidence: 99%